Enzymatic Production Of Non-Natural Nucleoside-5′-Monophosphates By A Thermostable Uracil Phosphoribosyltransferase (2018)
The use of enzymes as biocatalysts applied to synthesis of modified nucleoside-5′-monophosphates (NMPs) is an interesting alternative to traditional multistep chemical methods which offers several advantages, such as stereo-, regio-, and enantioselectivity, simple downstream processing, and mild reaction conditions. Herein we report the recombinant expression, production, and purification of uracil phosphoribosyltransferase from Thermus themophilus HB8 (TtUPRT). The structure of TtUPRT has been determined by protein crystallography, and its substrate specificity and biochemical characteristics have been analyzed, providing new structural insights into the substrate-binding mode. Biochemical characterization of the recombinant protein indicates that the enzyme is a homotetramer, with activity and stability across a broad range of temperatures (50–80 °C), pH (5.5–9) and ionic strength (0–500 mm NaCl). Surprisingly, TtUPRT is able to recognize several 5 and 6-substituted pyrimidines as substrates. These experimental results suggest TtUPRT could be a valuable biocatalyst for the synthesis of modified NMPs.